ALPOMISH” AND “YODGOR” EPIC POEMS: ARTISTIC FEATURES AND THEIR SIMILARITIES AND DIFFERENCES (International Educators Conference, 2025)
This article analyzes the artistic features, similarities, and differences of the epic poems “Alpomish” and “Yodgor” These epics are significant examples of Uzbek folk literature, reflecting national values, customs, and historical events through their heroes, plots, and artistic styles. The article explores the artistic style, characterization, and thematic aspects of each epic.